2018
DOI: 10.1002/nbm.4007
|View full text |Cite
|
Sign up to set email alerts
|

Connectomic imaging reveals Huntington‐related pathological and pharmaceutical effects in a mouse model

Abstract: Recent studies suggest that neurodegenerative diseases could affect brain structure and function in disease‐specific network patterns; however, how spontaneous activity affects structural covariance network (SC) is not clear. We hypothesized that hyper‐excitability in Huntington disease (HD) disrupts the coordinated structural and functional connectivity, and treatment with memantine helps to reduce excitotoxicity and normalize the connectivity. MRI was conducted to measure somatosensory activation, resting‐st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 80 publications
2
11
0
Order By: Relevance
“…ALFF and fALFF are low-level parameters. In rodents, they are most commonly used to compare across experimental groups (Yao et al, 2012;Chang et al, 2018;Wen et al, 2018).…”
Section: Amplitude Of Low Frequency Fluctuationsmentioning
confidence: 99%
“…ALFF and fALFF are low-level parameters. In rodents, they are most commonly used to compare across experimental groups (Yao et al, 2012;Chang et al, 2018;Wen et al, 2018).…”
Section: Amplitude Of Low Frequency Fluctuationsmentioning
confidence: 99%
“…For example, the use of volumetric MRI to assess striatal atrophy is one of the most sensitive imaging biomarkers in HD and, while detected in premanifest HDGCs, may rely on neuronal loss, which therapeutic intervention would precede ideally. DTI, functional MRI, and magnetic resonance spectroscopy may detect pathology at earlier stages than volumetric MRI, and NODDI affords sensitivity and better definition of the underlying neurobiological basis of pathology [19,39,92,93,[131][132][133][134][135]. Thus, using these MRI metrics together could provide interrelated information and may reduce noise inherent to each measure.…”
Section: Discussionmentioning
confidence: 99%
“…Memantine as a NMDA antagonist can reduce the excitotoxicity and normalize the brain connectivity [94]. Chidambaram, et al reported simultaneous blockade of NMDAR and suppression of PARP activity is necessary to ameliorate immune-excitotoxicity and improve bioenergetics in 3-NP induced neurodegeneration.…”
Section: Memantine: Coordinated Structural and Functional Connectivity Is Disrupted By Hyper-excitability In Hdmentioning
confidence: 99%